2021
DOI: 10.35808/ersj/2067
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of Digital Competenciees among Employees and Non-Working People of Generation Z in the Economy 4.0

Abstract: Purpose: The objective of this article is to identify and analyse self-assessment of digital competencies among employees, soldiers and Generation Z people who are not in employment, as well as its correlations with gender, generation, personality, place of residence, professional status, interest in professional military service, motivation, feeling of satisfaction of their expectations concerning employment/military service, as well as capacity to work in Economy 4.0. Design/Methodology/Approach: The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…As research has shown, the generation born since 2000 in Poland uses similar digital sources of job recruitment information as the rest of the world, but to a slightly lesser extent (RNL, 2020;European Commission, 2020;Kupczyk, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As research has shown, the generation born since 2000 in Poland uses similar digital sources of job recruitment information as the rest of the world, but to a slightly lesser extent (RNL, 2020;European Commission, 2020;Kupczyk, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, its importance seems crucial, against the background of the ongoing fourth industrial revolution and the development of the digital world (Volini et al, 2017;Lores Gómez et al, 2019). Especially since the level of digital competence in Poland is not high (European Commission, 2020), even in the young generation (Kupczyk, 2021). ICT substantially changed the shape of the world people were accustomed to.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the relevance of digital analysis is further supported by the work of (Garfinkel, 2010), who emphasized the need for standardized, modular approaches for data representation and forensic processing, which are essential for systematic analysis. Additionally, the study by Kupczyk (2021) focused on self-assessment of digital competencies among employees and soldiers, highlighting the correlation between digital competencies and the capacity for systematic analysis. The impact of digital analysis on decision-making and strategic planning is also evident in the study by (Nowacka & Rzemieniak, 2021), which discussed the influence of the VUCA (volatility, uncertainty, complexity, ambiguity) environment on digital competencies of management staff.…”
Section: Discussionmentioning
confidence: 99%
“…Nie oznacza to jednak, że problematyka identyfikacji i oceny potencjału kompetencyjnego nie jest analizowana na szczeblu ukształtowanych, doświadczonych pracowników (strona podażowa) (np. Kupczyk, 2021;Elliott-Engel, Westfall-Rudd, Seibel, Kaufman i Radhakrishna, 2021) bądź oczekiwań kompetencyjnych pracodawców (strona popytowa) (np. Szydło, Wiśniewska, Tyrańska, Dolot, Bukowska i Koczyński, 2021).…”
Section: Dyskusjaunclassified